A statistical analysis study on Dragon Textile Mills, Inc. - Martinez, Deanne Ambata (College of Engineering, 2002)
Dragon Textile Mills, incorporated is one of the most advanced and modern textile mills in the country. It is an automated, modern and efficient textile mill specializing in spinning using the Open-end rotor Spinning concept of producing high quality yarn. It was established in the year 1988 and currently employs more than 100 people inclusive of officers and Manila Staff. The statistical analysis study focuses on the finished package (yarn) in the Open-end Spinning section. Aside from being the last part in the production process, it is where the highest rate of defects is generated, determined using Pareto Analysis. The production starts from the Blowing, which involves the bale opening, cleaning and blending of bales and ends in packing. Quality monitoring is executed in almost every step, both manual and mechanical. Using Pareto Analysis, it has been found that the small package problem, contributing 84.12 percent of the total bad package problem must be addressed in order to solve the bad package problem in the Open-end Spinning section of DTMI. A small package is a defective package having its length and weight below the standard, which is 3.78 kg for count 7, 2.9 kg for count 10 and 2.1 kg for count 20. Three core problems affecting the variability in weight were identified using the Streamline Diagnosis diagram. These are the variability of the temperature affecting the strength of the package, variability in relative humidity and count variation. Three factors are derived from these problems and were used in the design of experiment. These are the count variation, variation in temperature and variation in the relative humidity. Through the use of 2 factorial design, two of the three factors, temperature and relative humidity, were known to have significant effect on the weight of the finished package. Using the Normal Probability Plot, the findings were strengthened. Using graphical analysis, high levels of temperature and relative humidity are preferred because both have lower deviation from the standard weight of the finished package for count 7. For count 10 and count 20 low levels of temperature and relative humidity are preferred since both have lower deviation from the standard weight of the finished package. The group, then, recommends to establish the levels of the factors with significant effects and maintain them. After the appropriate ranges of Temperature and Relative Humidity have been established and maintained, DTMI must conduct regular quality inspections in order to guarantee that the variability in the weight of the package has been minimized. If not, adjustments should be made to attain a better range of levels of Temperature and Relative Humidity, which will yield less weight variability in the finished product. This measure is a continual process over time since other factors might emerge or develop that might affect variability of the weight of the finished package.